Fostering Religious Inclusivism Attitudes in School Through Learning The Quran and Ḥadīth - Hudzaifah Achmad Qotadah; Iqbal Syafri; Adang Darmawan Achmad (International Journal of Islamic Thought and Humanities, 2022)
Education is a vitally essential social activity with the primary goal of enriching the social situation. Therefore, education that emphasizes building an inclusive and open attitude, particularly in religious matters, is crucial, particularly in the lives of a diverse society. This study aims to demonstrate how teaching selected passages from the Quran and the Ḥadīth in classrooms might help foster an inclusive mentality. This study used a qualitative approach with analytical descriptive research methods. A total of thirteen people participated in this study; eleven students from the Aliyah level and two educators from the MAN 1 Yogyakarta. The data was acquired through a combination of observation and semi-structured interviews. The study results indicated that the formation of inclusive religious attitudes through Quranic teaching and Ḥadīth could be accomplished using an integrative learning methodology based on historical approach, values analysis and case studies geared toward an inclusive model. Thus, students will automatically develop an inclusive and open attitude toward a variety of multicultural thoughts, including in matters of religion. As a result, it will allow them to build social groups of people living in harmony and may provide a way to solve various conflicts and hostility.